The role of Big Five personality domains and facets in musical sensibility: a twin study - Heidi Marie Umbach Hansen; Bruno Laeng; Olav Mandt Vassend; Nikolai Olavi Czajkowski; Tor Endestad; Anne Danielsen; Espen Røysamb (Scientific Reports)
Abstract Musical sensibility can be understood as a propensity to be emotionally and aesthetically engaged by music and may constitute a key feature of a multidimensional definition of musicality. Yet, the nature of this construct is only just beginning to be understood. In a sample of adult Norwegian twins (N = 2592), we aimed to establish whether interindividual variability in musical sensibility may partially be attributable to personality, both in terms of the Big Five personality domains and their lower-order facets, as well as the role of genes and environments. Phenotypic analyses demonstrated that the personality domains of open-mindedness (and the facet aesthetic sensitivity in particular), agreeableness (and the facet compassion), and negative emotionality were all significantly associated with and predictive of musical sensibility. Multivariate biometric twin models further revealed that these relations were driven mainly by genetic influences, accounting for 50–100% of the observed covariance, whereas non-shared environmental influences accounted for the rest. Moreover, genetic correlations of musical sensibility with personality traits were substantial, and particularly strong for open-mindedness, pointing to considerable overlap in the biological mechanisms underlying the two traits. These findings situate musical sensibility within a broader network of psychological dispositions, possibly linked together via common affective systems.